Fluctuating Asymmetry in Hybrids of Sibling Species, Drosophila ananassae and Drosophila pallidosa, Is Trait and Sex Specific - Vishalakshi, Chavali; Singh, Bashisth N (The Journal of heredity, 2009)
Due to inconsistent results of the empirical studies, the relationship between fluctuating asymmetry (FA, a measure of developmental stability) and interspecific hybridization has been the subject of intense debates. In the present study, we have assessed the impact of interspecific hybridization between 2 sibling species of Drosophila: Drosophila ananassae and Drosophila pallidosa on the levels of FA over 3 generations. Trait size of different morphological traits, namely, sternopleural bristle number, wing length (WL), wing to thorax (W/T) ratio, sex comb tooth number (SCTN), and ovariole number differed significantly among parental species and their hybrids of different generations in both the sexes. However, the levels of FA of different morphological traits were similar in parental species and their hybrids of different generations in males (except SCTN) and in females (except for WL and W/T ratio). These results are interpreted in terms of developmental stability as a function of a balance between the level of heterozygosity and the disruption of coadapted gene complexes.